THE USE OF MIND MAPPING IN TEACHING READING COMPREHENSION - Rissa San Risqiya (Eltin Journal : Journal of English Language Teaching in Indonesia, 2013)
It is reported by World Bank that Indonesian students’ readingcomprehension is very low. That is why, it is crucial to conduct a researchon appropriate techniques to develop students’ reading comprehension. Oneof them is mind mapping (MM). MM is a technique that can increase one’sability in note taking. It not only includes the key words of information orideas but also implements the use of colors and drawing, thus MM projectbecomes fun and enjoyable. The aim of this study is to observe theimplementation of MM in a class of first graders of a senior high school inBandung. For that reason , two meetings are observed. There are threeinstruments employed: students’ mind maps, observation (by observer andthe teacher), and open-ended questionnaire. From the data obtained, it isrevealed that there is improvement from the first meeting (90.4%) to thesecond one (94.6%) of the students mind maps. The MM can make thestudents recall their background knowledge and focus on their reading.Meanwhile, the questionnaires indicate that they are unfamiliar with thetechnique, yet they enjoy it. Therefore, MM can be considered to be analternative technique in teaching reading comprehension. KEYWORDS: mind mapping, open-ended questionnaire